2015
DOI: 10.3390/s150923653
|View full text |Cite
|
Sign up to set email alerts
|

Cuffless and Continuous Blood Pressure Estimation from the Heart Sound Signals

Abstract: Cardiovascular disease, like hypertension, is one of the top killers of human life and early detection of cardiovascular disease is of great importance. However, traditional medical devices are often bulky and expensive, and unsuitable for home healthcare. In this paper, we proposed an easy and inexpensive technique to estimate continuous blood pressure from the heart sound signals acquired by the microphone of a smartphone. A cold-pressor experiment was performed in 32 healthy subjects, with a smartphone to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
2
37
1
Order By: Relevance
“…To the best of our knowledge, the earliest platform considered for unobtrusive application was integration in a T-shirt with ECG electrodes at the wrists [22]. Other unobtrusive or mobile system can be mounted on wrists as wearable watches [20], upper arms [73], or ears [74]; attached to the chest as a patch [75] or a band [47]; and implemented through mobile phones [76,77] or weighing scales [19]. In particular, the BP watch would be one of the most popular platforms to implement the unobtrusive system.…”
Section: Unobtrusive Systemmentioning
confidence: 99%
“…To the best of our knowledge, the earliest platform considered for unobtrusive application was integration in a T-shirt with ECG electrodes at the wrists [22]. Other unobtrusive or mobile system can be mounted on wrists as wearable watches [20], upper arms [73], or ears [74]; attached to the chest as a patch [75] or a band [47]; and implemented through mobile phones [76,77] or weighing scales [19]. In particular, the BP watch would be one of the most popular platforms to implement the unobtrusive system.…”
Section: Unobtrusive Systemmentioning
confidence: 99%
“…The SVM algorithm has been used to estimate cuffless BP using heart sound signals, where acceptable BP measurement accuracy was achieved [ 33 ]. Similarly, in our study, the SVM algorithm was applied to PPG signal features to estimate cuffless BP.…”
Section: Discussionmentioning
confidence: 99%
“…An existing study reported that amplitude of S2 from hypertensive patients was higher than that from normotensive [2]. Increased BP also led to an increase in frequency of S2 [3], [4]. The relation between S2 and the arterial BPs from both systemic and pulmonary circulations has been confirmed in [5], [6], [7].…”
Section: Introductionmentioning
confidence: 86%